Evolving policies and the roles of public and private stakeholders in wastewater and faecal-sludge management in India, China and Ghana - Murray, Ashley; Mekala, G.D.; Chen, X. (Informa UK Limited, 2011)
In this article the authors document evolving attitudes, policies and roles of stakeholders in wastewater and faecal-sludge management in India, China and Ghana. In each country there is momentum for expanding not just access to sanitation at the household/community levels, but also for greater treatment and safe end-of-life management of human excreta. Governments are increasingly looking to engage the private sector, but models of engagement that make a compelling business case and instil confidence in cost recovery will have to emerge before the private sector takes an active role in wastewater and faecal sludge treatment in low-income countries.